Analysis of Learning Theories and Their Implications for Teaching and Student Outcomes in Elementary Schools - Baiq Yuni Wahyuningsih; Ni Made Yeni Suranti (Indonesian Publication Center, 2024)
This research aims to analyze the application of learning theory in learning and its implications for student's abilities and learning outcomes. The type of research used in this research is qualitative research, which uses the literature review or literature study method. Data collection techniques are carried out by searching for sources and constructing them from various sources, such as books, journals, and research that has been carried out previously. Primary research data comes from data directly related to the predetermined theme and can come from appropriate journal studies. In general, the results of the research show that: 1) The application of behaviorism learning theory can have an influence on learning which becomes focused and structured, 2) The application of cognitiveism learning theory shows that this learning theory can help students to improve their understanding of concepts, both in learning mathematics or other. Apart from that, the application of this learning theory can also help teachers to increase student activity in class, so that teachers do not play a full role in providing knowledge/information, but involve student activity in learning and 3) Constructivist learning theory, has an influence on students' critical thinking abilities so that they can improve the learning outcomes achieved. Learning that takes place in class becomes more effective.